Estudio de clima laboral e implementación de planes de en la Empresa Mundo Motriz de la ciudad de Quito, Ecuador - Cañadas Zurita, Estefania Soledad (2016)
Mundo Motriz S.A is a company which has as productive activity the repairmen of damaged or wrecked vehicles. Starting in February 2015, the organization faced a change in their management which included new managers and head officers. For these reason, the need to develop a diagnostic of the work environment has been identified. In this diagnostic, the administration change was analyzed. Also with this diagnostic information and data was gathered to feed an action plan which contributed on improving the current conditions of the work environment in the organization. For these task technical resources, materials and financial resources from the company has been used. The use of these resources helped in reaching the project objectives according to the plan. Within this study, we can see the results generated in the investigation for work environment in the company Mundo Motriz S.A. As well as the design and implementation of an action plan focused on improving the work environment of the company. Thus, emphasis was placed on two points. First, identifying any changes generated in the organization. Second, the valuation of the respective characteristics of the work environment through the systematization of experiences where our goal was gathering information, which is extracted from the different action plans, such as; campaigns expectation shots tests, analysis of results, the closing survey after evaluation, the improvement proposals plan and the implementation.